AGENESIS OF DORSAL PANCREAS AS INCIDENTAL FINDING IN A COVID-19 85-YEAR-OLD PATIENT: A CASE REPORT WITH A REVIEW OF LITERATURE - Branković, Marija; Gmizić, Tijana; Dukić, Marija; Lalatović, Jovana; Mrda, Davor (Medical Research, 2024)
Introduction: Polysplenia syndrome is a very rare congenital condition with multifactorial inheritance. It is characterized by the malposition of the thoracic and abdominal organs with or without vascular abnormalities. It comprises multiple cardiac, gastrointestinal, hepatosplenic, pancreatic and renal disorders. It is usually an incidental finding on abdominal ultrasound or computed tomography (CT) scan performed for other reasons. Patient review: In this case, an 85-year-old male patient is presented, who tested positive for coronavirus disease 2019 (COVID-19) infection and he was admitted to a hospital for bilateral COVID-19 pneumonia. Further, CT scan was performed and revealed polysplenia, various vascular abnormalities, gastrointestinal malformations and agenesis of the dorsal pancreas, so heterotaxy syndrome was diagnosed. Interestingly, this patient doesn’t have diabetes mellitus in spite of agenesis of the dorsal pancreas, neither he ever had pancreatitis. Conclusion: This present case shows that the quality of life in patients with polysplenia syndrome doesn’t have to be seriously impaired and that these patients can experience old age. Moreover, the awareness and prior knowledge of anomalies included in this syndrome are crucial in order to avoid complications during surgical and/or interventional procedures.